Tejiendo Redes, Construyendo Comunidad: El Poder de las Amistades Lésbicas - Vidal, María José Alonso Vidal (Cadernos de Gênero e Diversidade, 2025)
El artículo examina las relaciones de amistad que desde hace mucho tiempo se generan al interior del colectivo homosexual, resaltando su papel como construcciones identitarias desde las cuales ejercer una práctica de resistencia a las normas sociales que los estigmatizan. El texto se centra específicamente en las amistades lésbicas, entendiéndolas con un particular poder subversivo frente a la heteronormatividad. Finally, it reflects on how, once the rights for which the institutional gay and lesbian movement fought so hard had been won, the social integration of homosexuality may have led to the loss of the group’s transformative potential by prioritising the use of heteronormative institutions to the detriment of its alternative forms of relationship, which are beginning to disappear.This text adopts feminist autoethnography as a dissident research method that validates experiential knowledge as a legitimate source of knowledge. Through this lens, it explores the nexus between the personal and the political, highlighting its capacity to catalyse the transformation of society.